NILAI ANAK DAN PERSEPSI TERHADAP PENDIDIKAN ANAK SERTA HUBUNGANNYA DENGAN TINGKAT PENDIDIKAN ANAK PETANI (Studi Kasus di Kelompok Tani Giri Senang Kabupaten Bandung) - Devia Destriyani; Rani Andriani Budi Kusumo (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
The Giri Senang Farmer Group has members who on average have not completed 12 years of education. The purpose of this study is to determine the value of children for families, family perceptions of children's education, chindren’s education level, and the correlation between children's values and family perceptions of children's education with the level of children's education in the Giri Senang Farmer Group. This research uses a quantitative approach with survey methods and analysis using descriptive analysis. Determination of respondents using random sampling techniques, amounting to 34 respondents. The results showed that most of the agricultural laborers considered that children had more psychological values than social and economic values. Parents consider their children a blessing and their existence makes the family complete. Farm worker families' perceptions about children's education show that education is very important for children, but the educational level of farmworker family children in the Giri Senang Farmers Group is dominant only up to elementary school with a percentage of 45,83% and the lowest is at the college level with a percentage of 1,04%. In the correlation between children's values and family perceptions about children's education with the level of education of the family children of farm workers the Giri Senang Farmer Group has a very weak and insignificant correlation. Therefore, it is hoped that parents can actively motivate and provide insight into the importance of education for life.